Conflicts in Ecosystem Services Management: Analysis of stakeholder participation in Natura 2000 in Poland. Issue 117 (March 2021) - Maczka, Krzysztof; Matczak, Piotr; Jeran, Agnieszka; Chmielewski, Piotr Jerzy; Baker, Susan
Highlights: Conflict over conservation planning is linked to stakeholders' perspectives on loss of access to particular ES types. Conflict over cultural and provisioning ES are particularly noticeable. Natura 2000 management would benefit from an approach that recognises changes that site designation may make to ES. Learning opportunities are provided by stronger procedures for recording conflicts arising in stakeholder participatory forum. Abstract: The relationship between specific ecosystem services (ES) and different types of conflicts are explored to aid understanding of the barriers to effective biodiversity conservation management. Drawing from conflict theory, content analysis is undertaken of public documents generated during consultations about Natura 2000 management that were conducted in Poland between 2010−2015. Results show the links between conflict over conservation planning and stakeholders' perceptions of potential threats to their access to, and use of, particular ecosystem types. Cultural and provisioning ES generate more conflict, with conflict over cultural ES dominating. Conflict over the value of conservation itself was less prevalent, indicating a general agreement about the need for conservation planning. The lack of standardized procedures for reporting on public consultation process negatively effected institutional memory and limited the opportunities for learning lessons from past mistakes and from good practices.